Biomarker responses in mussels (Mytilus trossulus) from the Baltic Sea exposed to water-accommodated fraction of crude oil and a dispersant at different salinities - Turja, Raisa; Benito, Denis; Ahvo, Aino; Izagirre, Urtzi; Lekube, Xabier; Stankevičiūtė, Milda; Butrimavičienė, Laura; Soto, Manu; Lehtonen, Kari K. (Elsevier BV, 2023)
Highlights • The dispersant resulted in higher oil concentrations at the lower salinity conditions. • Exposure to chemically dispersed oil caused rapid PAH bioaccumulation in mussels. • Higher oil exposure concentrations were linked to elevated biological responses. • The use of dispersants in the Baltic Sea still needs to be carefully considered. Abstract Oil spills pose significant environmental risks, particularly in cold seas. In the Baltic Sea, the low salinity (from 0 to 2 up to 18) affects the behaviour of the spilled oil as well as the efficiency and ecological impacts of oil spill response methods such as mechanical collection and the use of dispersants. In the present study, mussels (Mytilus trossulus) were exposed under winter conditions (5 °C) to the water-accommodated fraction (WAF) of Naphthenic North Atlantic crude oil prepared by mechanical dispersion or to the chemically enhanced fraction (CEWAF) obtained using the dispersant Finasol OSR 51 at salinities of 5.6 and 15.0. Especially at the lower salinity, high bioaccumulation of polycyclic aromatic hydrocarbons was recorded in mussels in the CEWAF treatments, accompanied by increased biomarker responses. In the WAF treatments these impacts were less evident. Thus, the use of dispersants in the Baltic Sea still needs to be carefully considered.